Studying the Combined Effect of Biocharand Organic Matteron Soil Waterpermeability - زيدان, علي; عيد, هيثم; إبراهيم, محمد (Latakia University Journal -Biological Sciences Series, 2021)
This research was carried out at the Agricultural Scientific Research Station in Beit Kammouna, Tartous, in cooperation with the Faculty of Agriculture at Tishreen University, where it included testing of 9 treatments consisting of the interaction of 3 added levels of organic matter in the form of fermented cow manure (O0, O1, O2) and 3 levels of biochar (B0, B1, B2), on weight basis at the following ratios (0, 1 and 2%), for each of them in 14 liter lysimetric glass basins, where the soil mixtures in the glass basins were saturated with water, and left for (24 hours) to reach stabilization and to get read of gravity water. Then, equal volumes of water were added, (1 liter), to each basin and the volumes of percolated water from the basins were measured during the mentioned 4 incremental periods of time (1, 15, 30, and 60) minutes, for all treatments. The data was collected and tabulated according to the 4 mentioned time periods. The results showed that singular soil biochar additions achieved a positive increase in soil water permeability at all measurement times. Also, there was a great similarity in the effect of the singular additions of biochar and organic matter in increasing the water permeability of the soil under all measurement times, with significant supreme of the biochar at the same levels of added organic matter in increasing the soil permeability. As for the effect of integration between biochar and organic matter, it was clearly and positively shown to increase soil water permeability. And the combined treatment (O2B2) consisting of (2% organic matter + 2% biochar) in the soil, gave the highest value of water permeability with a clear significant difference in comparison with the control and all other experimental treatments.